Outcomes of Anterior Urethral Stricture Management in a Tertiary Care Hospital in Eastern Nepal - Thakur, Deepak K; Agrawal, Chandra S (Journal of Institute of Medicine Nepal, 2022)
Introduction The standard guidelines for the management of anterior urethral strictures categorizes as transurethral procedures (dilatation and urethrotomy) and open surgical procedures (urethroplasty). This study aims to find the extent and outcome of anterior urethral strictures managed in a tertiary care hospital in eastern Nepal. Methods It was a hospital- based cross-sectional study. Patients were evaluated preoperatively as per institutional protocol. The procedure was done either in local or spinal or general anesthesia with nasal intubation. At the end of the procedure, a 14Fr Silicon catheter was inserted per urethra and removed either on the next day, 2 weeks or 4 weeks post operatively depending upon the type of procedure done. Patients were asked to follow up postoperatively at 6 weeks and three months. Results Thirty-six cases were eligible. The mean age of the patients was 39.25±14.02 years. According to the etiology; 36.1% were iatrogenic, 30.6% traumatic, 25% were BXO/LS associated and 8.3% were infective respectively. Similarly, 61.1% of strictures were bulbar in location, 22.2% panurethral, 11.1% penile and 5.6% meatal. The mean length of the stricture was 4.26±4.22 cm (range 1-14 cm). Similarly, VIU was done in 47.2%, augmentation urethroplasty in 44.4% meatoplasty in 5.6% and anastomotic urethroplasty in 2.8% respectively. Complications occurred in 11.1% of cases. Conclusion Iatrogenic and traumatic etiologies were common for the anterior urethral stricture. Visual internal urethrotomy was the commonly performed procedure for the urethral stricture with excellent short-term outcome in highly selected cases. Augmentation urethroplasty using oral mucosa graft for long segment stricture has acceptable success rate and complications.